Film Animasi sebagai Medium Dokumentasi Kekayaan Alam, Intelektual, Budaya, dan Dinamika Sosial Politik - Ardiyansah Ardiyansah (Humaniora, 2012)
Animation is a medium that has the ability to represent a visual phenomenon as a whole. Animation is not just a work of image-driven, but the work depicted motion, as expressed by Norman McLaren, Canadian animator Academy Award winner. As the interpretation of the motion, the animation is not subject to the laws of nature, so there is no limitation including movements that cannot be done in the real world or recorded in the live-action movie. So is the characterization or characterizations in the animation can be so free and open more opportunities for exploration. This advantage makes the animation a favorite medium to draw the attention of the audience, especially in the growing era of digital animation technology. Animation is now not only used for entertainment purposes, but has penetrated other fields such as education, tourism, health care, and so on. As a cultural product, animation, as well as films and works of art of human culture in general, is a historical marker that describes the spirit of an era that functions inherent in the animated film documentation of socio-political dynamics of a nation in a given period. This paper describes the process of documentation of natural, intellectual, cultural and socio-political dynamics in countries that intensively utilize the medium of animation.